Constraints and frustration in the clathrin-dependent endocytosis pathway - Bruna-Gauchoux, Julie; Montagnac, Guillaume (Comptes Rendus Biologies, 2022)
Clathrin-dependent endocytosis is the major pathway for the entry of most surface receptors and their ligands. It is controlled by clathrin-coated structures that are endowed with the ability to cluster receptors and locally bend the plasma membrane, leading to the formation of receptor-containing vesicles budding into the cytoplasm. This canonical role of clathrin-coated structures has been repeatedly demonstrated to play a fundamental role in a wide range of aspects of cell physiology. However, it is now clearly established that the ability of clathrin-coated structures to bend the membrane can be disrupted. In addition to chemical or genetic alterations, many environmental conditions can physically prevent or slow membrane deformation and/or budding of clathrin-coated structures. The resulting frustrated endocytosis is not only a passive consequence but serves very specific and important cellular functions. Here we provide a historical perspective as well as a definition of frustrated endocytosis in the clathrin pathway before describing its causes and many functional consequences.